The KEEP SIMPLEST study: improving in-house delays and periinterventional management in stroke thrombectomy; a matched pair analysis - Schönenberger, Silvia; Kronsteiner, Dorothea; Ungerer, Matthias; Pfaff, Johannes; Schieber, Simon; Uhlmann, Lorenz; Heidenreich, Pia; Bendszus, Martin; Kieser, Meinhard; Wick, Wolfgang; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; et al. (Neurocritical care, 2019)
Background and Purpose: Although the treatment window for mechanical thrombectomy (MT) in patients with acute ischemic stroke (AIS) has been extended in recent years, it has been proven that recanalizing treatment must be administered as soon as possible. We present a new standard operating procedure (SOP) to reduce in-house delay, standardize periinterventional management and improve patient safety during MT. MethodsKEep Evaluating Protocol Simplification In Managing Periinterventional Light Sedation for Endovascular Stroke Treatment (KEEP SIMPLEST) was a prospective, single-center observational study aimed to compare aspects of periinterventional management in AIS patients treated according to our new SOP using a combination of esketamine and propofol with patients having been randomized into conscious sedation (CS) in the Sedation versus Intubation for Endovascular Stroke TreAtment (SIESTA) trial. Primary outcome was early neurological improvement at 24h using the National Institutes of Health Stroke Scale, and secondary outcomes were door-to-recanalization, recanalization grade, conversion rate and modified Rankin Scale (mRS) at 3 months.ResultsDoor-to-recanalization time (128.6 ± 69.47 min vs. 156.8 ± 75.91 min; p = 0.02), mean duration of MT (92.01 ± 52 min vs. 131.9 ± 64.03 min; p < 0.001), door-to-first angiographic image (51.61 ± 31.7 min vs. 64.23 ± 21.53 min; p = 0.003) and computed tomography-to-first angiographic image time (31.61 ± 20.6 min vs. 44.61 ± 19.3 min; p < 0.001) were significantly shorter in the group treated under the new SOP. There were no differences in early neurological improvement, mRS at 3 months or other secondary outcomes between the groups. Conversion rates of CS to general anesthesia were similar in both groups.ConclusionAn SOP using a novel sedation regimen and optimization of equipment and procedures directed at a leaner, more integrative and compact periinterventional management can reduce in-house treatment delays significantly in stroke patients receiving thrombectomy in light sedation and demonstrated the safety and feasibility of our improved approach.
Gesehen am 05.08.2019